PERBEDAAN HASIL BELAJAR PEMAHAMAN KONSEP MELALUI PENERAPAN STRATEGI PEMBELAJARAN BERBASIS SELF REGULATED LEARNING - Yowelna Tarumasely (STKIP PGRI SITUBONDO, 2020)
This study aims to determine whether there is a difference between the learning outcomes of students' understanding of the concept of learning theory before and after implementing self-regulated learning-based learning strategies. The research subjects were 46 PAK students in the second semester of the 2019/2020 academic year. Data collection using tests in the form of multiple choices to measure the learning outcomes of learning concept understanding. The method used is quantitative methods, data analysis using a Paired Sample t-test (paired-sample t-test). The results show that the average posttest score is greater than the pretest average value, this means that there is an increase in student learning outcomes after applying self-regulated learning-based learning strategies, the results also show that the significance obtained is 0.000, which is less than 0.05, with thus Ho was rejected and Ha accepted. This means that there is a significant difference between the learning outcomes of students' understanding of the concept of learning theory before and after implementing self-regulated learning-based learning strategies.